Factors associated with girl child marriage in Iran: a qualitative socio-ecological approach - Asma Pourtaheri; Mehrsadat Mahdizadeh; Mehrsadat Mahdizadeh; Hadi Tehrani; Hadi Tehrani; Jamshid Jamali; Jamshid Jamali; Nooshin Peyman; Nooshin Peyman (Frontiers in Public Health)
IntroductionGirl child marriage is an example of a human rights violation, the unfortunate consequences of which have raised growing concerns in the health system and have become a development challenge. Therefore, this research was conducted to identify the factors driving girl child marriage based on the Socio-Ecological Model.MethodsThe present qualitative study employed guided content analysis and a deductive approach to identify the driving factors behind girl child marriage in Bam City. Sampling was targeted among Women aged 15–30 got married under the age of 15, family members, informants, and policymakers. Data were collected through semi-structured interviews and analyzed using Hsieh and Shannon approach and MAXQDA software.ResultsThe data was classified into five categories: individual, interpersonal, organizational, community, and society. Individual factors were classified into biological, psychological, and demographic factors. Interpersonal factors were categorized into two categories: family structure, Ineffective interactions and social support. Organizational factors included Weakness in the education and care system. Community factors included the economic situation governing the society. The society factors were divided into two categories: Cultural and social factors governing the society, and Weakness in policy making and legislation.DiscussionThe findings showed that the socio-ecological model is a suitable framework for explaining the driving factors of child marriage. Girl child marriage is not merely a personal or familial decision; rather, it is influenced by the interactions of different systems that can either exacerbate or mitigate the issue. Consequently, the management, control, and prevention of Girl child marriage necessitate comprehensive efforts at regional, national, and international levels. In addition to creating platforms for the empowerment of girls at both national and regional levels, international policies can also foster a supportive environment.